Additional mechanisms conferring genetic susceptibility to Alzheimer’s disease - Calero, Miguel; Gómez-Ramos, Alberto; Calero, Olga; Soriano, Eduardo; Avila, Jesús; Medina, Miguel (Frontiers in Cellular Neuroscience, 2015)
Familial Alzheimer's disease (AD), mostly associated with early onset, is caused by mutations in three genes (APP, PSEN1 and PSEN2) involved in the production of the amyloid  peptide. In contrast, the molecular mechanisms that trigger the most common late onset sporadic AD remain largely unknown. With the implementation of an increasing number of case-control studies and the upcoming of large-scale genome-wide association studies (GWAS) there is a mounting list of genetic risk factors associated to common genetic variants that have been associated to sporadic AD. Besides APOE, that presents a strong association with the disease (OR 4), the rest of these genes have moderate or low degrees of association, with OR ranging from 0.88 to 1.23. Taking together, these genes may account only for a fraction of the attributable AD risk and therefore, rare variants and epistastic gene interactions should be taken into account in order to get the full picture of the genetic risks associated to AD. Here, we review recent whole-exome studies looking for rare variants, somatic brain mutations with a strong association to the disease, and several studies dealing with epistasis as additional mechanisms conferring genetic susceptibility to AD. Altogether, recent evidence underlines the importance of defining molecular and genetic pathways and networks rather than the contribution of specific genes.